The predictive value of multiple electrode platelet aggregometry for postoperative bleeding complications in patients undergoing coronary artery bypass graft surgery - Woźniak, Sebastian; Woźniak, Karolina; Hryniewiecki, Tomasz; Kruk, Mariusz; Różański, Jacek; Kuśmierczyk, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction: Postoperative bleeding is one of the most serious complications of cardiac surgery and requires transfusion of blood or blood products. Acetylsalicylic acid (ASA) and clopidogrel (CLO) are the two most commonly used antiplatelet agents; when used in combination (i.e., as dual antiplatelet therapy [DAPT]), they exert a synergistic effect. Dual antiplatelet therapy, however, significantly increases the risk of postoperative bleeding. The effect of antiplatelet therapy can be monitored by platelet aggregation testing. One of the most commonly methods used for assessing platelet reactivity is multiple electrode aggregometry (MEA) which can be performed with the use of Multiplate analyzer. Although the method has long been used in interventional cardiology to assess the effect of antiplatelet therapy, it is not available at cardiac surgery departments as a standard diagnostic procedure. The aim of the study was to establish the frequency of bleeding complications following coronary artery bypass graft (CABG) surgery in patients on single antiplatelet therapy (SAPT) and patients on DAPT and to determine the usefulness of routine measurement of platelet responsiveness before CABG surgery in patients receiving antiplatelet therapy. Material and methods: A consecutive cohort of 200 patients referred for elective surgical treatment of stable coronary artery disease was enrolled (100 consecutive patients on SAPT [ASA 75 mg/day] and 100 consecutive patients on DAPT [ASA 75 mg/day + CLO 75 mg/day]). All subjects continued their antiplatelet therapy until the day before surgery. For each subject, platelet aggregation testing in the form of an ASPI test and an ADP test was performed on the Multiplate analyzer. Each subject underwent coronary artery bypass grafting surgery. For the primary and secondary endpoints in our study we adopted the definition provided in ‘Standardised Bleeding Definitions for Cardiovascular Clinical Trials: A Consensus Report from the Bleeding Academic Research Consortium’ (‘Circulation’, 2011) for BARC type 4 bleeding (i.e. CABG-related bleeding). Results: An ROC curve was constructed for the ASPI test and ADP test for a total of 200 patients. No significant correlations were demonstrated between the ASPI test results and either the primary endpoint or the secondary endpoints. A correlation was found between the ADP test results and the composite primary endpoint and each of the secondary endpoints. The primary endpoint of major postoperative bleeding occurred in 16 subjects. From the ROC curve, we established the optimal cut-off value for the ADP test of 26 U at sensitivity of 72%, specificity of 69%, positive predictive value of 69.90%, and negative predictive value of 71.13%. Conclusions: In patients on antiplatelet therapy, an ADP test result of < 26 U is strongly predictive of serious bleeding compli-cations after CABG surgery. The MEA ADP test allows to identify the group of patients at an increased risk of postoperative bleeding.